ON-FARM GROWER-FRIENDLY NURSERY TECHNIQUE FOR ACCLIMATIZATION OF TISSUE-CULTURED BANANA SEEDLINGS - Wong, K.F.; Suhaimi, O.; Fatimah, K. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Banana is one of the common fruit preferences in the world. The market demand for this crop increasing year round. Tissue-cultured banana seedlings are getting widely used as planting materials among the growers for its quality assured properties, particularly for commercial plantation. However, most of the small scale growers are still using conventional planting sources (water suckers and sword suckers). They do not prefer tissue-cultured seedlings due to its expensive price, delicate to handle and often result in high post-transplanting mortality rate. The considerably high cost is due to the process of producing the tissue-cultured seedlings at the nursery stage (acclimatization). Even at the nursery stage, the conventional acclimatization process of the plantlets in the nursery results in non-uniformity of establishment and high mortality rate. The research was conducted to develop a nursery technique that will improve these drawbacks in order to improve greater acceptance and responsive level for the growers towards tissue-cultured seedlings. Based on the results, the developed technique has increased the survival rate (reducing mortality rate) of seedlings as compared to the conventional technique. In addition, this developed technique can be adopted on-farm instead of using protected nursery as conventionally practiced. Using this technique, the seedlings would be more easily adapted to the farm after transplanting. Ordinary farmers prefer younger seedlings (10-15cm in height) for planting as they grow faster than that of older seedlings with common quality (15-25cm in height). Girth size of seedlings would be the higher consideration in meeting the requirement for transplanting purpose. The developed technique has shown better growth performance in both height and girth parameters in the first 36 days as compared to conventional technique. Meaning that this helps to shorten the nursery period and create an alternative standard for seedlings to be transplanted.